Differences in Gaze Fixation Location and Duration Between Resident and Fellowship Sonographers Interpreting a Focused Assessment With Sonography in Trauma. Issue 1 (28th February 2020) - Bell, Colin R.; Szulewski, Adam; Walker, Melanie; McKaigney, Conor; Ross, Graeme; Rang, Louise; Newbigging, Joseph; Kendall, John
Abstract: Objectives: We quantified the gaze fixation duration of resident and fellowship sonographers interpreting a prerecorded focused assessment with sonography in trauma (FAST). We hypothesized that all sonographers would fixate on each relevant anatomic relationship but that the duration of fixation would differ. Methods: We conducted a cross‐sectional study collecting and analyzing the gaze fixations of a convenience sample of current resident and fellowship sonographers. All sonographers viewed a standardized FAST video, and their gaze fixations were recorded using a Tobii X3‐120 eye‐tracking bar. Gaze fixations over nine anatomic regions of interest (ROIs) were identified. These were assessed for normality and analyzed using the Wilcoxon rank sum test at an alpha of 0.05 and Bonferroni correction p value of <0.0034. The chi‐square test and Pearson's correlation were performed to assess statistical association. Results: The gaze fixation recordings of 24 resident and eight fellowship sonographers were suitable for analysis. Fourteen of the 24 resident sonographers viewed all ROIs in the FAST, whereas all eight fellowship sonographers viewed each of the nine relevant ROIs. Five ROIs were identified over which at least one resident sonographer did not have a gaze fixation. No statistically significant difference was identified between groups. Resident sonographers gaze fixated over the left upper quadrant (LUQ) splenorenal interface for a median (interquartile range) of 10.64 (9.73–11.60) seconds. The fellowship group viewed the same ROI for 8.43 (6.64–8.95) seconds (p < 0.003). All participants viewed this ROI. No other ROIs had a statistical difference. Conclusion: Five ROIs were identified that were not visually interrogated by all resident sonographers. Only 14 of 24 resident sonographers visually interrogated every area in the FAST, whereas all fellowship sonographers interrogated every ROI. A statistically significant difference was found in gaze fixation duration between resident and fellowship sonographers in one ROI. Further study is required for gaze fixation assessment to become a tool for the interpretation component of point‐of‐care ultrasound.